2016
DOI: 10.1371/journal.pone.0150215
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Water Fraction Is Transiently Reduced after a Single Mild Traumatic Brain Injury – A Prospective Cohort Study in Collegiate Hockey Players

Abstract: Impact-related mild traumatic brain injuries (mTBI) are a major public health concern, and remain as one of the most poorly understood injuries in the field of neuroscience. Currently, the diagnosis and management of such injuries are based largely on patient-reported symptoms. An improved understanding of the underlying pathophysiology of mTBI is urgently needed in order to develop better diagnostic and management protocols. Specifically, dynamic post-injury changes to the myelin sheath in the human brain hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 82 publications
8
56
0
1
Order By: Relevance
“…These are inherently difficult to compare directly because of differences in study populations, methodology, time points and brain region of interest analysed. Among longitudinal studies, four used DTI26–29 and one used myelin water fraction (MWF) 30. One article found imaging consistent with clinical data, with radial diffusivity increased and fractional anisotropy (FA) decreased at post injury day 2 (PID) with normalisation by 14 days after injury 26.…”
Section: Diffusion Tensor Imaging/diffusion Mrimentioning
confidence: 92%
See 1 more Smart Citation
“…These are inherently difficult to compare directly because of differences in study populations, methodology, time points and brain region of interest analysed. Among longitudinal studies, four used DTI26–29 and one used myelin water fraction (MWF) 30. One article found imaging consistent with clinical data, with radial diffusivity increased and fractional anisotropy (FA) decreased at post injury day 2 (PID) with normalisation by 14 days after injury 26.…”
Section: Diffusion Tensor Imaging/diffusion Mrimentioning
confidence: 92%
“…However, others found changes in FA varied depending on region of interest and showed increased MD at chronic time points 31. MWF was reduced at 3 days after injury, tended to be decreased at day 14 and normalised by day 60 30. Diffusion kurtosis imaging showed changes from controls at 1 day after injury and persisting at day 8, but recovery of symptoms and cognition occurred between 1 and 8 days after injury 29…”
Section: Diffusion Tensor Imaging/diffusion Mrimentioning
confidence: 99%
“…Beyond MS, myelin water imaging has been used to study many other neurological disease applications include neuromyelitis optica , schizophrenia and first episode psychosis , phenylketonuria , autism , stroke , neurofibromatosis , Niemann–Pick disease , primary lateral sclerosis , amyotrophic lateral sclerosis , concussion , and Krabbe disease . Other spinal cord applications are also feasible, for example, a recent study of cervical spondylotic myelopathy demonstrated a correlation between MWF in the dorsal columns and functional measures of myelin through somatosensory evoked potential latency times .…”
Section: In Vivo Applications Of Myelin Water Imaging In Research Andmentioning
confidence: 99%
“…Myelin water fraction (MWF), defined as the fraction of the total signal which has T 2 < 40 milliseconds at 3 Tesla, has been histologically validated as a marker of myelin density in human tissue, 30–32 and has good scan‐rescan reproducibility (coefficient of variation 4% in cerebral white matter) 33 . MWI has been used to investigate myelin in a wide range of diseases including multiple sclerosis, neuromyelitis optica spectrum disorder, schizophrenia, Niemann‐Pick disease, prenatal alcohol exposure, amyotrophic and primary lateral sclerosis, Krabbe disease, autism, stroke, and traumatic brain injury 34–47 . Rapid myelination has been demonstrated in early childhood and adolescence using multicomponent driven equilibrium single pulse observation of T 1 and T 2 (mcDESPOT), an alternate approach to MWI using a steady‐state acquisition 48–53 .…”
Section: Introductionmentioning
confidence: 99%
“…33 MWI has been used to investigate myelin in a wide range of diseases including multiple sclerosis, neuromyelitis optica spectrum disorder, schizophrenia, Niemann-Pick disease, prenatal alcohol exposure, amyotrophic and primary lateral sclerosis, Krabbe disease, autism, stroke, and traumatic brain injury. [34][35][36][37][38][39][40][41][42][43][44][45][46][47] Rapid myelination has been demonstrated in early childhood and adolescence using multicomponent driven equilibrium single pulse observation of T 1 and T 2 (mcDESPOT), an alternate approach to MWI using a steadystate acquisition. [48][49][50][51][52][53] Adult multi-echo T 2 -based MWF atlases in both brain and cervical spinal cord have recently been published, 54,55 but, to our knowledge, no such atlases exist for children.…”
Section: Introductionmentioning
confidence: 99%